Populasi Bakteri Tanah Pada Berbagai Rizofer Tanaman Karet (Hevea Brasiliensis) di Sumatra Utara - Praizer Pasaribu, Kevin; Apriliya, Indah (Jurnal Ilmiah Pertanian ( JIPERTA), 2025)
The Ultisol soil, which dominates the North Sumatra region, is characterized by sour and nutrient poverty, so it requires additional interventions to support crop cultivation, including rubber plants (Hevea brasiliensis). One potential approach is the use of soil microorganisms as biological fertilizers, especially nitrogen-anchoring bacteria and phosphate solvents. This literature review aims to examine the population of soil bacteria in the rhizosphere zone of rubber plants and their ecological role in increasing plant fertility and productivity. Data was obtained from 25 scientific sources, including national and international journals, as well as reference books published between 2000 and 2024. The results showed that bacteria such as Azotobacter, Azospirillum, Rhizobium, Bacillus, and Pseudomonas dominate the rubber rhizosphere and have the ability to regulate nitrogen fixation, phosphate dissolution, growth hormone production, and pathogen biological control. The success of the implementation of biofertilizers is largely determined by the suitability of microorganisms with the conditions of the local agroecosystem. Therefore, exploration of North Sumatra-specific microbes is important as the basis for the development of more efficient and sustainable fertilization strategies.